Retracing the Past through Historical Fantasy Novel: The Poppy War - Marizka S, Andini; Sari, Winda Setia (LINGUISTIK TERAPAN, 2024)
Historical genre and fantasy genre each have its own ups and downs in their recognition and acceptation in the field of literature. This research explored the mixture of both of the genres, the historical fantasy genre. This research aimed to examine the historical representations and its authenticity in The Poppy War novel. The research was conducted by using the approach from McArthur (2008) related to the method on how to represent the past as a historical fantasy novel, as well as how authentic the historical representation by using the approach from Groce & Groce (2005). This research was done using qualitative research design in the form of textual analysis. The result showed that the novel used historical details and referred to historical figures and events as the ways of representing the history. The authenticity of the historical reference can be confirmed by the similarity of the data found in the novel with the secondary and tertiary sources. This research concluded that this novel can be used as a media to learn about historical events that happened during the Second Sino-Japanese War. However, readers needed to remember that the novel is historical fantasy novel that contains fantastical elements that helped the story progressed.